The Afterlife of Poetics - Korwin-Piotrowska, Dorota (Tematy i Konteksty, 2020)
The article presents contemporary debates concerning poetics, the heritage of structuralism as well as new research areas. It presents some of the fundamental arguments against poetics in its traditional sense and attempts to analyse and problematize them. In conclusion, the author postulates adopting a changed attitude towards the current terminology, including practical aspects in the study of poetics and also maintaining a multidimensional development of the discipline.